IgG4-related lung disease with pulmonary lesions and recurrent pleural effusion: A case of report - Ning Xia; Wei Wang; Wei Zhang; Yan Li; Xiu-Hong Nie (Radiology Case Reports)
We report a rare case of IgG4-related lung disease (RLD) with pulmonary lesions and recurrent pleural effusion to improve the diagnosis and treatment of this disease. A 60-year-old man was admitted to hospital for cough and dyspnea. CT scan showed a right lower lobe intrapulmonary mass with unilateral right-sided pleural effusion. Histology revealed no malignant findings. After 1 year, the patient re-admitted to our hospital with high serum level of IgG4 and IgE concentrations. CT scan demonstrated partial resolution of intrapulmonary mass and right-sided pleural effusion, while concurrently revealing interval development of substantial left-sided pleural effusion. The patient was diagnosed with IgG4-RLD by biopsy finally. This is a first case report of IgG4-RLD with intrapulmonary lesions accompanied by asynchronous, rapidly accumulating bilateral pleural effusions. Clinicians should consider the possibility of IgG4-RLD with intrapulmonary lesions accompanied by asynchronous, rapidly growing bilateral pleural effusion, particularly after rigorously excluding common diseases.